Quantum dynamic properties of photon-added trio coherent state in two-mode Jaynes-Cummings model - Le Thi Hong, Thanh; Trương, Minh Đức (Hue University Journal of Science: Natural Science, 2022)
In this paper, we studied the quantum dynamic properties via the two-mode Jaynes-Cummings (JC) model where an effective two-level atom interacts with a field in a photon-added trio coherent state (PATCS). The quantum dynamic properties of the atom and the field were investigated via the photon distribution function, the second-order correlation function of the same and different modes, and the probability of finding the atom in the excited state in the cavity. The results show the dynamic properties of the atom and the non-classical ones of the field in the PATCS. In addition to the factors that affect these dynamic properties, such as the original field strength, the role of adding photons to the modes of the field in the PATCS is important when compared with the field in the original state as the trio coherent state.